2022
DOI: 10.24831/jai.v50i1.39949
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Hasil Benih Padi Hibrida pada Tiga Galur CMS dengan Sumber Sitoplasma yang Berbeda

Abstract: Padi hibrida F1 dihasilkan dari persilangan antara galur mandul jantan/cytoplasmic male sterile (GMJ/CMS) dan galur pemulih kesuburan (restorer/R). Kalinga dan Gambiaca adalah tipe galur CMS yang berhasil dikembangkan di Indonesia selain tipe Wild Abortive (WA). Penelitian ini bertujuan untuk mempelajari pengaruh tetua betina dengan sumber sitoplasma berbeda terhadap hasil benih padi hibrida pada 30 kombinasi padi hibrida baru. Percobaan dilakukan di BB Padi Subang, Jawa Barat pada MK 2021, menggunakan rancang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It related to research (Fadzli et al, 2022) that the row ratio and spacing of the pollen parent and seed parent have a distinct effects on the hybrid seed yield. Wibowo et al (2022) reported that differences in the cytoplasmic type in CMS also influenced seed yield. In this study, the effects of differences in row ratio and plant spacing combinations were insignificant on plant height (A and R lines), tillers number of A-line, panicle of exertion rate, filled and unfilled grains per panicle, and outcrossing rate (Table 3).…”
Section: Effects Of Interactionmentioning
confidence: 99%
“…It related to research (Fadzli et al, 2022) that the row ratio and spacing of the pollen parent and seed parent have a distinct effects on the hybrid seed yield. Wibowo et al (2022) reported that differences in the cytoplasmic type in CMS also influenced seed yield. In this study, the effects of differences in row ratio and plant spacing combinations were insignificant on plant height (A and R lines), tillers number of A-line, panicle of exertion rate, filled and unfilled grains per panicle, and outcrossing rate (Table 3).…”
Section: Effects Of Interactionmentioning
confidence: 99%